The Relationship Between the Perception of Fixed Orthodontic Appliance Usage and Interest in Malocclusion Treatment Among Students - Puspitasari, Yustisia; Chotimah, Chusnul; Salim, Andi Nur Annisa (Jurnal Kesehatan Manarang, 2024)
Orthodontic care needs are increasing and also vary; in addition to the demand need for maintenance, there are socioeconomic factors and the availability of maintenance services. Perceptions regarding the use of simplified orthodontic devices from aesthetic aspects are generally the primary motivation of patients to carry out malocclusion treatment. In orthodontic treatment, perception can be seen from the aesthetic and functional aspects. Orthodontic comes from the word ortho, which in Greek means normal, straight, or correct, while dontos means teeth. Background Orthodontic care is the need to improve the health of the oral cavity, oral cavity function, and personal appearance. The success of orthodontic care not only depends on the ability and technique used but is influenced by the interest and motivation factors of the patient himself/herself. Most individuals who carry out orthodontic care are usually driven by personal care related to appearance and aesthetics. Most malocclusion has an effect on a person's self-image. Therefore, orthodontic treatments must be able to improve the individual aesthetic. The research objective is to find out the correlation between the perception of the use of simplified orthodontic devices and the interest in Malocclusion Care for FKG students of the Universitas Muslim Indonesia. This research was descriptive quantitative research using cross-sectional data. The statistical test used was the Chi-Square test. The sample in this study consisted of 121 samples. Data analysis was tested using a chi-square test with a degree of meaning α = 0.05. The statistical analysis results show that the value of P 0.419 then HA is unaccepted, which means there is no correlation between the perception of the use of Orthodontic device and interest in the treatment of malocclusion. There is no correlation between the perception of using the Orthodontic Device and Malocclusion Care in FKG students of the Universitas Muslim Indonesia.